Kajian Pemanfaatan Koleksi Jurnal Internasional UPT Perpustakaan Universitas Diponegoro melalui Perspektif Bibliometrik pada Tesis Sekolah Pascasarjana tahun 2018-2019 - Fivenda Ayu Amalia; Yanuar Yoga Prasetyawan (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
The aim of this study is to determine the use of international journal collection subscribed by Diponegoro University Library through a bibliometric perspective on the Magister student thesis School of Postgraduate published in 2018 and 2019. This study analyzes the usage of international journal collection on the theses of School of Postgraduate students, frequently used journals and authors, and the level of obsolescence of international journal collections. This study used quantitative method with data collection techniques using documentation analysis from institutional repository or directly at the School of Postgraduate library. This study examines 221 theses titles from four study programs using descriptive statistical analysis with Microsoft Excel. The findings show that the School of Postgraduate students who compiled the thesis published in 2018 and 2019 have utilized international journal collection. Masters in Environmental Sciences 17,16%, Masters in Epidemiology 14,86%, Masters in Information System 37,12%, and Master in Energy 26,68%. The journal titles that are often used by each study program in sequence are Journal of Cleaner Production, PLOSone, Expert System with Application, and Energy Policy. The names of authors that are often mentioned are Li, Y., Sacco, R., L., Chen, J.-K., and Champier, D. Futhermore, more than 50% of the literature that utilizes international journal collection subscribed by Undip is literature with current category.